2010
DOI: 10.1007/s11144-010-0242-7
|View full text |Cite
|
Sign up to set email alerts
|

[(C18H37)2(CH3)2N]7[PW11O39]: a temperature-controlled phase transfer catalyst for olefin epoxidation

Abstract: A novel temperature-controlled phase transfer catalytic system based on [(C 18 H 37 ) 2 (CH 3 ) 2 N] 7 [PW 11 O 39 ] for olefin epoxidation was demonstrated. The reaction was conducted in a non-chlorinated solvent of ethyl acetate with hydrogen peroxide. The catalyst was easily recovered and reused even ten cycles without loss in activity and selectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Gas-phase epoxidation of BD has been realized on silver catalysts [5,6]. At the same time, it is reasonable to consider a liquid-phase oxidation of BD to EpB because of a newly developed low-cost manufacturing of H 2 O 2 from O 2 and H 2 gases and the appropriate interest to studies of epoxidation of terminal and cyclic olefins [6][7][8][9][10][11][12][13][14][15][16]. Specific problem of BD is its strong reactivity with respect to side transformations.…”
Section: Introductionmentioning
confidence: 99%
“…Gas-phase epoxidation of BD has been realized on silver catalysts [5,6]. At the same time, it is reasonable to consider a liquid-phase oxidation of BD to EpB because of a newly developed low-cost manufacturing of H 2 O 2 from O 2 and H 2 gases and the appropriate interest to studies of epoxidation of terminal and cyclic olefins [6][7][8][9][10][11][12][13][14][15][16]. Specific problem of BD is its strong reactivity with respect to side transformations.…”
Section: Introductionmentioning
confidence: 99%
“…Hua et al studied a reusable phosphotungstate catalyst composed of cetyltrimethylammonium cations and [PW 11 O 39 ] 7– ; 51.8% H 2 O 2 conversion and 73% product selectivity could be achieved, and they found that benzaldehyde was the main byproduct. Similarly, Zhao et al developed a phase-transfer catalyst for the epoxidation of olefins. High styrene conversion and product selectivity were achieved when catalyzed by [(C 18 H 37 ) 2 (CH 3 ) 2 N] 7 [PW 11 O 39 ], composed of the bulky organic cation and keggin-type lacunary [PW 11 O 39 ] 7– , and the catalyst could be recycled easily after the temperature dropped due to its temperature-dependent solubility.…”
Section: Introductionmentioning
confidence: 99%
“…Among reported alkene epoxidations catalyzed by polyoxometalates, tungsten-based polyoxometalate catalytic systems showed high activity and selectivity. Many groups [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] have been involved in this topic in the world. However, most of these transformations catalyzed by polyoxometalates were homogeneous reactions, which suffered the difficulty of separation and reuse of the catalysts.…”
Section: Introductionmentioning
confidence: 99%